Synthesis of Nano-Flakes Ag•ZnO•Activated Carbon Composite from Rice Husk as A Photocatalyst under Solar Light - Anh-Tuan Vu; Thi Anh Tuyet Pham; Thi Thuy Tran; Xuan Truong Nguyen; Thu Quynh Tran; Quang Tung Tran; Trong Nghia Nguyen; Tuan Van Doan; Thao Duong Vi; Cong Long Nguyen; Minh Viet Nguyen; Chang-Ha Lee (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
This study aimed to synthesize Ag•ZnO•Activated carbon (Ag•ZnO•AC ) composite from rice husk for degradation of dyes. The deposition of Ag and ZnO on AC led to decreasing the surface area and pore volume of Ag•ZnO•AC composite. In addition, when Ag and ZnO were dispersed on activated carbon, the Ag•ZnO flakes became denser and tighter, but the particle size of Ag became smaller from 5 to 7 nm. The photocatalytic ability of Ag•ZnO•AC composite was evaluated by degradation of Janus Green B (JGB) and compared with that of AC, ZnO, Ag•ZnO, and ZnO•AC samples. The effects of catalyst dosages, pH values, and initial dye concentrations on photocatalytic degradation were investigated in detail. The Ag•ZnO•AC composite had a high degradation efficiency of 100% in 60 min, showing the reaction rate of 0.120 min-1 and degradation capacity of 17.8 mg/g within 20 min. The photocatalytic performance of the Ag•ZnO•AC composite was also evaluated by cyclic test and the degradation of other persistent dyes such as Methylene Blue, Tartrazine, Congo Red, and organic compounds (Caffeine and Bisphenol A). Based on the experimental results, the possible destruction route of JGB by the as-synthesized Ag•ZnO•AC composite was suggested. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).